Beer Polyphenols and Menopause: Effects and Mechanisms—A Review of Current Knowledge. (17th August 2017) - Sandoval-Ramírez, Berner Andrée; Lamuela-Raventós, Rosa M.; Estruch, Ramon; Sasot, Gemma; Doménech, Monica; Tresserra-Rimbau, Anna
Abstract : Beer is one of the most frequently consumed fermented beverages in the world, and it has been part of the human diet for thousands of years. Scientific evidence obtained from the development of new techniques of food analysis over the last two decades suggests that polyphenol intake derived from moderate beer consumption may play a positive role in different health outcomes including osteoporosis and cardiovascular risk and the relief of vasomotor symptoms, which are commonly experienced during menopause and are an important reason why women seek medical care during this period; here, we review the current knowledge regarding moderate beer consumption and its possible effects on menopausal symptoms. The effect of polyphenol intake on vasomotor symptoms in menopause may be driven by the direct interaction of the phenolic compounds present in beer, such as 8-prenylnaringenin, 6-prenylnaringenin, and isoxanthohumol, with intracellular estrogen receptors that leads to the modulation of gene expression, increase in sex hormone plasma concentrations, and thus modulation of physiological hormone imbalance in menopausal women. Since traditional hormone replacement therapies increase health risks, alternative, safer treatment options are needed to alleviate menopausal symptoms in women. The present work aims to review the current data on this subject.